Case–control study demonstrates that surfactant without intubation delayed mechanical ventilation in preterm infants. (26th January 2017) - Vik, Sigrid Dannheim; Vik, Torstein; Lydersen, Stian; Støen, Ragnhild
Abstract: Aim: This Norwegian study explored whether administering surfactant without intubation (SWI) delayed the need for early mechanical ventilation and reduced respiratory and nonrespiratory complications in infants born before 32 weeks of gestational age. Methods: We compared 262 infants admitted to a level‐three neonatal intensive care unit: 134 born before the introduction of SWI on 1 December 2011 were in the control group and 128 infants born after this date were in the study group. Results: The proportion of infants treated with surfactant did not differ between the groups, but mechanical ventilation before 72 hours of life was lower in the study group than the control group, with an odds ratio (OR) of 0.58 and a 95% confidence interval (CI) of 0.35–0.96. Fewer study group infants needed supplemental oxygen at 28 days of life. One study infant and nine control infants had intraventricular haemorrhage grades 3–4 and, or, cystic periventricular leukomalacia (OR 0.10, 95% CI 0.01–0.83). These results were strengthened in analyses restricted to surfactant‐treated infants and the proportion needing supplemental oxygen at 36 weeks was reduced. Conclusion: Surfactant without intubation reduced the need for early mechanical ventilation and major brain injuries in infants born at <32 weeks of gestation.